ORGANIZATION OF CONTINUOUS LEARNING AND LEARNING IN PROGRAMMING AND ROBOTICS USING THE CONCEPT OF A PERSON’S WHOLE LIFE COURSE - Yunusova Gulshod Nazihovna; Abdullayeva Shaxlo Ibrohimjon qizi; Jo’rabayeva Nigora; Nurmatov Oqiljon Odiljon o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
This article promotes the idea of continuous teaching of programming and robotics. From a young age of 5-6, the idea of implementing robotics exercises in Lego Mindstorms, further complicating them in further education, and practically integrating computer programs that move a real robot or machine into C++, C#, Python programming language, or the use of ready-made applications has been developed. In conjunction with organizing the entry of a teacher into the programming world by teaching robotics, it serves to provide insight into the basics of its programming and to improve programming skills. Robotics, which is taught in additional education, in turn strengthens knowledge of programming. And their continuous training together is also consistent with the implementation of the concept of "teaching a person all his life."